Analysis of Risk Factors for the Incidence of Dermatitis - Heramuliati, Heramuliati; Abdullah, Asnawi; Nurjannah, Nurjannah; Maifrizal, Maifrizal (GLOBAL HEALTH SCIENCE GROUP, 2024)
In the initial survey, it was discovered that most of the fishermen from Kembang Tanjong sub-district and Simpang Tiga sub-district were traditional fishermen and used very little personal protective equipment, which made it possible for dermatitis to occur in fishermen. They stated that using personal protective equipment such as gloves, shoes and head coverings could hinder movement. When they work, personal hygiene is also given less attention due to the habit of fishermen spending the night in the middle of the sea when fishing, so fishermen do not prioritize their personal hygiene. The purpose of this study is to determine the analysis of risk factors for the incidence of dermatitis in fishermen on the coast of Kembang Tanjong District and Simpang Tiga District, Pidie Regency. This type of research is descriptive analytic using a cross sectional design. The population and sample in this study were all research subjects and objects studied, namely 298 fishermen. Data analysis in this study was univariate, bivariate and multivariate. The results of the study showed that there were five variables that had a relationship with the incidence of dermatitis in fishermen, namely personal hygiene (P-value 0.000), knowledge (P-value 0.000), use of PPE (P-value 0.000), education (p-value 0.007) and history of allergies (P-value 0.000) and for variables that do not have a significant relationship, namely the role of health workers (p-value 0.760) and length of service (pvalue 0.60. Conclusion: It is hoped that the results of this research can be used as input to improve health promotion by providing education to fishermen and other communities about dermatitis in the Kembang Tanjong and Simpang Tiga sub-districts in order to raise awareness among fishermen and other communities to make efforts to prevent dermatitis such as personal hygiene and use of PPE while working.